1986
DOI: 10.1111/j.1360-0443.1986.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow in Marijuana Smokers

Abstract: SummaryRegional cerebral blood flow measurements were performed with the 133Xenon inhalation technique in 17 chronic marijuana smokers and 16 age‐and sex‐matched controls. There were no significant differences between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Functional neuroimaging studies suggest that resting global, prefrontal and ACC blood flow are lower in cannabis users than in controls (Mathew et al 1986 ;Tunving et al 1986 ;Block et al 2000b ;Lundqvist et al 2001 ;Sevy et al 2008 ;Sneider et al 2008). The localization of resting state differences between users and controls to these regions is broadly consistent with data from neuropsychological studies.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Functional neuroimaging studies suggest that resting global, prefrontal and ACC blood flow are lower in cannabis users than in controls (Mathew et al 1986 ;Tunving et al 1986 ;Block et al 2000b ;Lundqvist et al 2001 ;Sevy et al 2008 ;Sneider et al 2008). The localization of resting state differences between users and controls to these regions is broadly consistent with data from neuropsychological studies.…”
Section: Discussionsupporting
confidence: 73%
“…The imaging methods used were 133 Xe-SPECT (Mathew et al 1986 ;Tunving et al 1986 ;Lundqvist et al 2001 Sneider et al 2008). In a group of nine chronic cannabis users, assessed within 1 week of drug cessation, Tunving et al (1986) found a reduction in global CBF relative to controls that did not correlate with the duration of cannabis consumption.…”
Section: Non-acute Effects On Resting State Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, such theories do not explain the apparent proclivity for partial posterior circulation strokes in young patients. Mathew and Wilson 21,22 have studied regional cerebral blood flow patterns in the setting of numerous drugs of abuse, including marijuana. They used a 133 Xe inhalation technique in which clearance of the isotope was measured for 10 minutes by detectors mounted in a helmet worn by the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Initial measures (days 0 and 7) revealed the former to have increased cerebral blood volume in the right frontal region, bilateral temporal regions, and the cerebellum, a finding that was only applicable to the left temporal region and cerebellum by day 28. The remaining 5 imaging studies that compared cannabis users and nonusers comprise 3 with SPECT and 2 with PET and showed a mixed picture of regional or global cerebral blood flow: no differences, 25 reduced, [26][27][28] or both reduced and increased depending on anatomical location 29 in the cannabis users.…”
Section: E14mentioning
confidence: 99%